Strategi Manajemen SDM Dalam Meningkatkan Profesionalisme Dan Kualitas Layanan Di Café Dan Resto Padi’s Banyuwangi: - Hafifah , Yayuk Nur; Pratama , Dicky Adityo; Suryaningtyas , Kurnia (Tractare: Jurnal Ekonomi-Manajemen, 2025)
This study aims to analyze human resource management (HRM) strategies in improving employee professionalism and service quality at Padi’s Café and Restaurant, Banyuwangi. The research employs a descriptive qualitative approach with data collected through interviews, observations, and documentation. The results indicate that HRM practices remain informal, including direct recruitment, basic training, and informal performance evaluation. Employee professionalism is reflected in friendly attitudes and work responsibility but is inconsistent during peak hours. Service quality is considered adequate, yet improvements are needed in service speed and consistency